(untitled) (IPS Journal of Public Health, 2022)
Naturally, fish is highly perishable, thus its careful handling, prompt preservation and processing are vital factors to consider in order to avoid economic and nutritional losses in fish trade. This study was carried out to ascertain the presence and the quantity of three organochlorine pesticides (Endosulfan, DDT and Heptachlor) and two organophosphate pesticides (Dichorvos and Chlorpyrifos) used in the preservation of two different smoke-dried fish samples namely; Catfish (Clarias gariepinus) and Bonga shad fish (Ethmalosa fimbriata) sold in Ogwashi-Uku market, Aniocha South, Delta State, Nigeria. Gas chromatography (GC – MS) technique was used to determine the pesticide residues in both samples and the results showed positive identification of these pesticides in the samples ranging from 0.4212ppm-0.1760ppm (Endosulfan), 1.2317ppm-0.7270ppm (DDT), 1.1265ppm-0.7019ppm (Heptachlor), 0.0536ppm-0.4274ppm (Chlorpyrifos) with the exception of Dichlorvos which was below determination level (BDL) in the catfish sample but present at 0.0415ppm value in the Bonga shad sample. This study also found that there are possible health implications such as; immune suppression, hormone disruption, diminished intelligence, reproductive abnormalities and cancer in humans.